Exogenous melatonin affects photosynthesis in characeae Chara australis - Lazár, Dušan; Murch, Susan J; Beilby, Mary J; Al Khazaaly, Sabah (Plant signaling & behavior, 2013)
Melatonin was found in the fresh water characeae Chara australis. The concentrations (~4 μg/g of tissue) were similar in photosynthesizing cells, independent of their position on the plant and rhizoids (roots) without chloroplasts. Exogenous melatonin, added at 10 μM to the artificial pond water, increased quantum yield of photochemistry of photosystem II by 34%. The increased efficiency appears to be due to the amount of open reaction centers of photosystem II, rather than increased efficiency of each reaction center. More open reaction centers reflect better functionality of all photosynthetic transport chain constituents. We suggest that melatonin protection against reactive oxygen species covers not only chlorophyll, but also photosynthetic proteins in general.
Keywords: Photosynthesis; Chlorophyll; Photosystem II Protein Complex; reaktivní formy kyslíku; chloroplasty; Characeae; photosynthesis; melatonin; Light-Harvesting Protein Complexes; chlorofyl; Chara; Antioxidants; Reactive Oxygen Species; antioxidancia; fotosystém II (proteinový komplex); antioxidants; reactive oxygen species; transport elektronů; světlosběrné proteinové komplexy; Chloroplasts; fotosyntéza; Electron Transport; chlorophyll fluorescence; Melatonin